The Utilization of a Mixture of Palm Oil and Shellfish Industrial Waste in Producing Paving Block: Producing Paving Block - Aisyah, Siti Aisyah; Imelda, Donna; Busrizal; Hakim, Muhamad Abdul (Jurnal Keteknikan Pertanian, 2024)
The population growth in Indonesia will lead to increased demands in the development sector.This growth must be balanced with environmentally friendly development practices. Therefore,there is a need for alternative uses of industrial waste into other finished materials. Concretebricks (Paving blocks) are one of the building construction materials that function to cover orpave the ground. Boiler ash is one of the solid wastes of the palm oil industry which comes fromthe remains of burning shells and fibers in boiler machines. Palm oil shells are also one of thesolid wastes of the palm oil industry which comes from the separation between fiber and shellswhich occurs in the Light Tenera Dust Separator machine. (LTDS). Seashells can be considereda form of solid waste. According to the research findings, paving blocks treated with S1 and S2exhibit water absorption capacities that comply with SNI 03-0691-1996 standards, whichstipulate a maximum of 8% for C grade, suitable for pedestrian use. Paving blocks treated withS3 also meet the SNI 03-0691-1996 standards, with a maximum absorption of 10% for D grade,which is ideal for covering plants and home gardens. Lower water absorption rates indicatehigher quality paving blocks. Variance analysis reveals that water absorption capacitysignificantly impacts the quality of paving blocks. The compressive strength test showed thatpaving blocks with S2 treatment had the highest strength, averaging 2.10 MPa. The highpercentage of boiler ash, which acts as a partial binder for the sand, is the reason for this. Thelowest compressive strength, averaging 1.01 MPa, is observed in paving blocks treated with S3.This is because of the significant amount of shell ash, which contains the chemical compoundsilica, similar to sand. Additionally, according to SNI 03-0691-1996, the compressive strengthtest results for paving blocks treated with S1, S2, and S3 do not meet the minimum requirementof 8.5 MPa. Analysis of variance indicates that the compressive strength of paving blocks variessignificantly.